Advancement of Electroadhesion Technology for Intelligent and Self‐Reliant Robotic Applications. (28th April 2022) - Rajagopalan, Pandey; Muthu, Manikandan; Liu, Yulu; Luo, Jikui; Wang, Xiaozhi; Wan, Chaoying
Abstract : The growing need for automation in industries has foreseen drastic advancements in the development of soft robotics in the areas of navigation systems, textiles, healthcare, and biometric monitoring. Electroadhesion (EA)‐based robotic applications benefit from ultralow power consumption, low maintenance, choices in versatile surfaces, sustainable life cycles, applicability in harsh and vacuum environments, and exteroceptive/proprioceptive abilities. It is of scientific and technological importance to comprehend the sequence of developments in working mechanisms, modeling, and materials to explore its full potential for future intelligent robotics systems. This review provides an all‐inclusive roadmap of EA technology from its inception to unprecedented developments and complex relationships across multidisciplines, viz., robotics, solid and fluid mechanics, electrostatics, haptics, space technologies, nanotechnology, and IoT. Abstract : The article summarizes the detailed roadmap of advances in the electroadhesion technology in the last 100 years on mechanism, theoretical structure, materials, and application framework. The detailed report presents a core interdisciplinary account on the advanced related technologies supportive to the researchers in the field of robotics, haptics, space technologies, and IoT.